Competing Inequalities? On the Intersection of Gender and Ethnicity in Candidate Nominations in Indian Elections. Issue 3 (28th April 2016) - Jensenius, Francesca R.
Abstract : Quotas for women and ethnic minorities are implemented to increase diversity in political institutions, but, as they usually target only one group at a time, they may end up increasing the inclusion of one under-represented group at the cost of another. Recent work has emphasized the institutional underpinnings of the variation in such outcomes. In this article I show how the intersectional effects of quotas may also vary within the same institutional context, as changes in the pressure to include excluded groups interact with the informal opportunity structures within political parties. Looking at the nomination of female candidates across India over time, I show that, as the efforts to include more women in politics intensified, much of the increase in female candidates occurred in constituencies reserved for ethnic minorities. This pattern may in part be the result of parties resisting changes to existing power hierarchies by nominating women at the cost of the least powerful male politicians, but can also be seen as evidence that minority quotas have created a political space that is more accessible to women.